Czech Honeydew Honeys-A Potential Source of Local Medical Honey with Strong Antimicrobial Activity - Pudelka, Ludovit; Sleha, Radek; Janovska, Sylva; Radochova, Vera; Bostik, Pavel (Pharmaceuticals (Basel, Switzerland), 2024)
An increasing resistance of microbes to antibiotics, the emergence of multidrug-resistant and extremely resistant strains, and the long time needed to develop new antibiotics are driving the search for additional sources of antibacterial agents. The aim of the study was to compare the efficacy of Czech honeys with already available pharmaceutical agents containing medicinal honey, and to perform basic biochemical analysis of Czech samples, including detection of undesirable chemical substances. The results showed strong antibacterial activity of Czech honeydew honeys compared to the control group, especially against G+ pathogens, with an average MIC of 9.44% compared to 17.54%, and comparable activity against G- of 16.48% versus 16.66%. In addition to the strong antibacterial activity, this study confirmed the safety and quality of Czech honeys and helped to select the character of a possible source for in vivo testing and subsequent clinical trials.
Keywords: hydrogen peroxide; polyphenolic compounds; honeydew; antibacterial effect